Statin therapy in chronic viral hepatitis: a systematic review and meta-analysis of nine studies with 195, 602 participants. (1st January 2021) - Vahedian-Azimi, Amir; Shojaie, Sajad; Banach, Maciej; Heidari, Farshad; Cicero, Arrigo F. G.; Khoshfetrat, Masoum; Jamialahmadi, Tannaz; Sahebkar, Amirhossein
Abstract: Background: Conflicting data suggest that statins could cause chronic liver disease in certain group of patients, while improving prognosis in those with chronic viral hepatitis (CVH). Purpose: To quantify the potential protective role of statins on some main liver-related health outcomes in clinical studies on CVH patients. Data Sources: The search strategy was explored by a medical librarian using bibliographic databases, from January 2015 to April 2020. Data synthesis: The results showed no significant difference in the risk of mortality between statin users and non-users in the overall analysis. However, the risk of mortality significantly reduced by 39% in statin users who were followed for more than three years. Moreover, the risk of HCC, fibrosis, and cirrhosis in those on statins decreased by 53%, 45% and 41%, respectively. Although ALT and AST reduced slightly following statin therapy, this reduction was not statistically significant. Limitations: A significant heterogeneity among studies was observed, resulting from differences in clinical characteristics between statin users and non-users, study designs, population samples, diseases stage, comorbidities, and confounding covariates. Conclusion: Not only long-term treatment with statins seems to be safe in patients affected by hepatitis, but also it significantly improves their prognosis.